HCV knowledge among a sample of HCV positive Aboriginal Australians residing in New South Wales. Issue 5 (28th May 2017) - Wilson, Hannah; Brener, Loren; Jackson, L. Clair; Saunders, Veronica; Johnson, Priscilla; Treloar, Carla
Abstract: Australian Aboriginal and Torres Strait Islanders are overrepresented in both the prevalence and incidence of the hepatitis C (HCV). HCV knowledge has been associated with a range of positive health behaviours. HCV knowledge has previously been investigated as a single construct; however examining different knowledge domains (i.e. transmission, risk of complications, testing and treatment) separately may be beneficial. This study investigated whether having greater HCV knowledge in different domains is associated with self-reported positive health behaviours. 203 Aboriginal people living with HCV completed a survey assessing HCV knowledge, testing and care, lifestyle changes since diagnosis and treatment intent. Respondents' knowledge was relatively high. Greater knowledge of risk of health complications was associated with undertaking more positive lifestyle changes since diagnosis. Respondents testing and treatment knowledge was significantly associated with incarceration, lifestyle changes since diagnosis and future treatment intentions. This study illustrates the importance of ensuring that knowledge is high across different HCV domains to optimise a range of positive health behaviours of Aboriginal people living with HCV. Future health promotion campaigns targeted at Aboriginal people living with HCV could benefit from broadening their focus from prevention to other domains such as testing and treatment.